International inter-laboratory analyses of food folate - Prapasri Puwastien (2018)
An international inter-laboratory performance of food folate assay was evaluated using soybean flour, fish powder and breakfast cereal which were prepared as test materials. These materials were sent to 34 laboratories, which were asked to use their routine methods of food folate analysis, and 26 laboratories (76%) worldwide returned their assay data. Although trienzyme extraction has been recommended for folate extraction before the assay, this method of folate extraction was used in only nine laboratories, and eight laboratories still performed a single enzyme treatment using folate conjugase. Of these 26 laboratories, 20 used microbiological assay (17 used Lactobacillus casei), four used an HPLC-UV detection method, one LC-MS and one radiobinding assay for folate analysis, indicating a wide variety of folate detection methods. Among 17 laboratories where L. casei microbiological assay was performed, the inter-laboratory coefficient of variations of these test materials was 24%, 35% and 24% for soybean flour, fish powder and breakfast cereal, respectively, indicating that a valid comparison of the values between the laboratories may be difficult. Our observations suggest that for food folate analysis, it is important to standardize the methods of folate extraction and detection, and the use of reliable reference materials should be encouraged among laboratories worldwide. © 2004 Elsevier Inc. All rights reserved.